Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1371/journal.pone.0193564
|View full text |Cite
|
Sign up to set email alerts
|

Montelukast for bronchiolitis obliterans syndrome after lung transplantation: A randomized controlled trial

Abstract: Bronchiolitis obliterans syndrome (BOS) remains the major problem which precludes long-term survival after lung transplantation. Previously, an open label pilot study from our group demonstrated a possible beneficial effect of montelukast in progressive BOS patients with low airway neutrophilia (<15%), and already on azithromycin treatment, in whom the further decline in pulmonary function was attenuated. This was, however, a non-randomized and non-placebo controlled trial. The study design is a single center,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…In a pilot study, montelukast has been tried in fibroproliferative post-lung transplant BOS and showed slowing of decline in FEV 1 [87]. However, a recent trial by Ruttens et al showed no additional survival benefit with montelukast compared with placebo [88]. Several studies reported that a combination of inhaled fluticasone, azithromycin, and montelukast (FAM) could be an effective treatment in patients with BOS [89].…”
Section: Efficacy Of Azithromycinmentioning
confidence: 99%
“…In a pilot study, montelukast has been tried in fibroproliferative post-lung transplant BOS and showed slowing of decline in FEV 1 [87]. However, a recent trial by Ruttens et al showed no additional survival benefit with montelukast compared with placebo [88]. Several studies reported that a combination of inhaled fluticasone, azithromycin, and montelukast (FAM) could be an effective treatment in patients with BOS [89].…”
Section: Efficacy Of Azithromycinmentioning
confidence: 99%
“…Sixty-one percent of patients were free from CLAD progression, defined by a less than 10% decrease or increase in FEV 1 . However, a small, randomized controlled study by the same group failed to demonstrate a survival benefit or difference in rate of change of FEV 1 with montelukast compared with placebo (56). Findings in this study were likely limited by a sample size of only 30 patients.…”
Section: Ras As Irreversible Decline Of Fevmentioning
confidence: 66%
“…227 In this study, the rate of FEV 1 decline slowed after the introduction of montelukast. 227 A subsequent randomized placebo-controlled trial of montelukast for treatment of BOS was published as a conference abstract, 228 although a peerreviewed publication is still not available at the time of this review. Montelukast reportedly had no effect on the evolution of lung function in the overall cohort.…”
Section: Montelukastmentioning
confidence: 99%
“…However, for patients with stage 1 BOS, there was a significant benefit of montelukast on lung function relative to placebo. 228 Montelukast is generally well tolerated and relatively inexpensive, making a trial of therapy a reasonable option for CLAD.…”
Section: Montelukastmentioning
confidence: 99%